Everything in Nature is in Intellect: Forms and Natural Teleology in Ennead 6.2.21 (and elsewhere). - Noble, Christopher Isaac (Phronesis, 2021)
According to a straightforward reading of Enn. 6.2.21, all principles (logoi) in nature have their origin in corresponding features of a divine Intellect. But interpreters have often advocated more restricted readings of Intellect's contents. These restricted readings are based in part on other textual evidence, and in part on the concern that a more expansive reading would require Intellect to think objects that are of trivial value ('the value problem') or whose purposes depend upon facts about sensible reality to which it has no access ('the teleology problem'). I argue that restricted readings are not well supported, and that Plotinus is committed to his more expansive conception of Intellect's contents by his understanding of Plato's paradeigmatism.